Online Games and Students' Learning Interest On English Learning Achievement - Kamarudin, Kamarudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to test whether there is online game and student interest on English learning achievement in MTs NW Asmaul Husna. The sample was 20 students. This study used two independent variables, namely online games (X1) and student interest (X2), while the dependent variable was learning achievement (Y). The data used in this study was primary data in the form of questionnaires with 20 respondents. This research method uses quantitative. The data analysis technique used in this study was simple regression analysis. The results of this study are known F value of 1.390 <compared to the F-table of 3.59. So, it can be concluded that H0 is accepted and Ha is rejected which means that there is no significant influence between online games (X1) and interest (X2) on student learning achievement (Y)